2018
DOI: 10.1039/c7cc08349a
|View full text |Cite
|
Sign up to set email alerts
|

Long-life sodium/carbon fluoride batteries with flexible, binder-free fluorinated mesocarbon microbead film electrodes

Abstract: Home-made fluorinated mesocarbon microbeads (F-MCMBs) were synthesised and employed in sodium batteries. Flexible, binder-free F-MCMB film electrodes were fabricated to enhance the cycle stability, and 65 cycles were achieved, which is the longest lifespan reported thus far. Nitrogen-doped graphene nanosheets (N-GNS) were also introduced as a catalyst, with the aim of lowering the voltage gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Except for primary lithium batteries, fluorinated carbon is also widely investigated in the field of solar cells, lithium/sodium-ion batteries, and lithium-sulfur batter-ies [95][96][97][98][99]. Jeon et al reported an edge-selectively fluorinated graphene nanoplatelets (FGnPs) with a maximized charge polarization and an enhanced chemical stability, which demonstrates superb stability/cycle life for dye-sensitized solar cells (FF: 71.5%; Jsc: 14.44 mA cm −2 ; Voc: 970 mV; PCE: 10.01%) and lithium-ion batteries (650.3 mA h g −1 at 0.5 ∘ C, charge retention of 76.6% after 500 cycles) [95].…”
Section: Other Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for primary lithium batteries, fluorinated carbon is also widely investigated in the field of solar cells, lithium/sodium-ion batteries, and lithium-sulfur batter-ies [95][96][97][98][99]. Jeon et al reported an edge-selectively fluorinated graphene nanoplatelets (FGnPs) with a maximized charge polarization and an enhanced chemical stability, which demonstrates superb stability/cycle life for dye-sensitized solar cells (FF: 71.5%; Jsc: 14.44 mA cm −2 ; Voc: 970 mV; PCE: 10.01%) and lithium-ion batteries (650.3 mA h g −1 at 0.5 ∘ C, charge retention of 76.6% after 500 cycles) [95].…”
Section: Other Batteriesmentioning
confidence: 99%
“…Jeon et al reported an edge-selectively fluorinated graphene nanoplatelets (FGnPs) with a maximized charge polarization and an enhanced chemical stability, which demonstrates superb stability/cycle life for dye-sensitized solar cells (FF: 71.5%; Jsc: 14.44 mA cm −2 ; Voc: 970 mV; PCE: 10.01%) and lithium-ion batteries (650.3 mA h g −1 at 0.5 ∘ C, charge retention of 76.6% after 500 cycles) [95]. Liu et al employed the home-made fluorinated mesocarbon microbeads (F-MCMB) for sodium-ion batteries [99]. Binder-free of F-MCMB film electrode delivered an initial discharge capacity of 647.8 mA h g −1 and obtained a good lifespan of over 65 cycles at 0.05 ∘ C. The results demonstrated that micro-structure design could improve the electrochemical performance of Na/CFx cells.…”
Section: Other Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li/S batteries configuration with GO membrane exhibited a cyclic capacity decay rate of 0.23%/cycle and superb anti‐self‐discharge properties. Similarly, GO network coating the carbon fluorides (CF x ) particles can confine active fluorine during cycles in Na/CF x system, corresponding to the enhanced cycle stability and lifespan …”
Section: Introductionmentioning
confidence: 99%
“…More often than not, a conventional electrode consists of a electroactive material (with Cu and Al as current collector for anode and cathode, respectively), a polymer binder and conductive additives. The inhomogeneous blend of the additives and electroactive materials influences the diffusion paths of ions and electrons in the electrode and lowers the weight/volume energy density of the overall lithium batteries or sodium batteries . In this contribution, we hypothesize that CuS microspheres may serve as electroactive materials to build a sodium battery without a binder and current collector.…”
Section: Introductionmentioning
confidence: 99%